The Influence of Budget Participation, Asymmetric Information, and Organizational Commitment on Budgetary Slack with Budget Emphasis as a Moderating Variable in the Langkat Regency Government - Asmara, Rizqy Winny (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the influence of budget participation, asymmetric information and organizational commitment on the budget gap with budget emphasis as a moderating variable in the Langkat Regency Government. Data were collected through questionnaires to structural officials who carry out budgeting in 56 OPDs in Langkat Regency, totaling 224 people selected using the purposive sampling method and 212 questionnaires filled in from the research from January to April 2024,The analysis method uses SEM based on the SmartPLS Version 4.1 variant. The research instrument has passed the validity and reliability test. The research results show that budget participation, asymmetric information and organizational commitment have a significant positive effect on the budget gap, budget participation becomes significantly negative on the budget gap, when budgetary emphasis moderates the relationship between the two, while information asymmetry and organizational commitment are not significantly related to the budget gap when the emphasis is on budget gaps. Budget as a moderating variable.